Association of genetic variants of membrane receptors related to recognition and induction of immune response with Helicobacter pylori infection in Ecuadorian individuals. (23rd April 2014) - Cabrera‐Andrade, A.; López‐Cortés, A.; Muñoz, M. J.; Jaramillo‐Koupermann, G.; Rodriguez, O.; Leone, P. E.; Paz‐y‐Miño, C.
Summary Helicobacter pylori (Hp) has a worldwide distribution showing its higher prevalence of infection in developing countries. Toll‐like receptors (TLRs) and C‐type lectin receptors (CLRs) are proteins that recognize pathogen‐associated molecular patterns (PAMPs) and initiate an innate immune response by promoting growth and differentiation of specialized hematopoietic cells for host defense. Gastric infections led by Hp induce a Th‐1 cellular immune response, regulated mainly by the expression of IFN‐γ. In this retrospective case‐control study, we evaluated the TLR1 1805T/G, TLR2 2029C/T, TLR4 896A/G, CD209 ‐336A/G and IFNGR1 ‐56C/T polymorphisms and their relationship with susceptibility to Hp infection. TLR1 1805T/G showed statistical differences when the control (Hp‐) and infected (Hp+) groups (P = 0.041*) were compared; the TLR1 1805G allele had a protective effect towards infection (OR = 0.1; 95% CI = 0.01‐0.88, P = 0.033*). Similarly, the IFNGR1 ‐56C/T polymorphism showed statistical differences between Hp+ and Hp– (P = 0.018*), and the IFNGR1 ‐56TT genotype exhibited significant risk to Hp infection (OR = 2.9, 95% CI = 1.27‐6.54, P = 0.018*). In conclusion, the pro‐inflammatory TLR1 1805T and IFNGR1 ‐56T alleles are related with susceptibility to Hp infection in Ecuadorian individuals. The presence of these polymorphisms in individuals with chronic infection increases the risk of cellular damage and diminishes the cellular immune response efficiency towards colonizing agents.